Eco-design furniture and interior elements: aesthetics and innovation of splitting waste rattan weaving and production efficiency - Sumarno, Sumarno; Budi Prasetyo, Raden Ersnathan (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
Rattan is a natural material with high fiber content.Â Rattan is cut into various sizes and types to be utilized. The process of cutting and slicing generally leaves waste in the form of elongated rattan hearts of irregular shapes and sizes. The amount is large, almost 30%, and is not utilized. However, waste from the splitting process in the rattan industry is usually disposed of through burning, leading to substantial waste. Therefore, this study aims to reduce rattan splitting waste through weaving techniques and then use it as a basis for innovation in furniture products and interior elements. The study was conducted using an experimental research method to produce woven sheets. Karen weaving has been applied to materials with similar characteristics, such as lidi, vetiver, and bamboo. Data were obtained through observation, interviews, and documentation. Data analysis, with inferential analysis, tests the hypothesis by generalizing. Following the weaving experiment, natural coloring and interior product design were conducted. The design process included sketching, creating shop drawings, modeling, and bringing the design to life through prototypes. The results consist of woven rattan fiber strip sheets with a striped pattern, light brown color, textured, somewhat rigid, yet flexible enough to be folded or rolled lengthwise. Various techniques can be applied to crafting products, such as gluing, bending, rolling, folding, and sewing. The most effective application of woven rattan fiber sheets is fixed attachment on a flat surface with a flat direction. The contribution of research results can add alternative materials for the creation of craft products, furniture, and interiors made from rattan waste woven sheets. These rattan fiber strip sheets can be applied in 2D and 3D homeware product designs, serving decorative and protective functions.